Nasakh dalam Sunnah dan Kajian Multikulturalisme: Tafsir Adaptif dalam Konteks Indonesia - Aurizan Himmi Azhar; Abid Nurhuda; Thariq Aziz Thariq Aziz; Muhammad Faqihuddin Ismail (Jurnal Sosial Humaniora dan Pendidikan, 2026)
This article discusses the concept of nasakh in the Sunnah and its relevance to adaptive Qur’anic exegesis in the Indonesian multicultural context. The main issue is how nasakh, often understood as abrogation, can be reframed as an instrument of flexibility within Islamic law that supports Islam as a mercy to all creation (rahmatan lil-‘alamin). This research employs a qualitative-descriptive approach by analyzing classical ulumul Qur’an literature, Sunnah, and contemporary exegesis. The findings reveal that nasakh in the Sunnah is not merely abrogation but a gradual strategy (tadarruj) in the formation of Islamic law. Concrete examples include the prohibition of temporary marriage (mut‘ah) and the change in the law regarding grave visitation. The wisdom of nasakh includes safeguarding welfare, ensuring justice, providing convenience, and testing faith. Meanwhile, multicultural tafsir emphasizes tolerance, justice, and religious freedom, as seen in Indonesian scholars’ interpretations of verses prohibiting insults to other deities (Q. al-An‘am:108), freedom of belief (Q. al-Kahf:29, Q. Yunus:99), and justice toward non-Muslims (Q. al-Mumtahanah:8, Q. al-Māidah:8). The integration of these two perspectives demonstrates that the concept of nasakh can serve as an adaptive exegesis paradigm supporting harmony within Indonesia’s plural society.